2012
DOI: 10.1180/claymin.2012.047.3.03
|View full text |Cite
|
Sign up to set email alerts
|

Relative coherent stacking potential of fundamental particles of illite-smectite and its relationship to geological environment

Abstract: Interstratified illite-smectite (I-S) occurring authigenically in diverse earth crust environments reacts toward more illite-rich phases as temperature increases. For that reason, I-S is used for geothermometry when prospecting for hydrocarbons or ore mineral deposits. This study develops the mathematical relations for characterizing the coherent stacking potential of fundamental particles (FP) using the expandability ratio K, where K is defined as (%SMAX –; %SXRD)/%SMAX. The ratio can be applied to differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…TEM analyses have shown that the fibrous illite has a complex crystal structure, whereby a 'single' crystal is composed of a stack of crystallites termed fundamental particles (Nadeau, 1985;Kang et al, 2012). A possible explanation of the change in illite composition with depth is that the fundamental particles within the illite fibres continue to thicken after the period of initial growth.…”
Section: Controls On Illite K-contentmentioning
confidence: 99%
See 1 more Smart Citation
“…TEM analyses have shown that the fibrous illite has a complex crystal structure, whereby a 'single' crystal is composed of a stack of crystallites termed fundamental particles (Nadeau, 1985;Kang et al, 2012). A possible explanation of the change in illite composition with depth is that the fundamental particles within the illite fibres continue to thicken after the period of initial growth.…”
Section: Controls On Illite K-contentmentioning
confidence: 99%
“…consists of alumino-silicate layers joined by nonexpandable K-rich layers with a minimum thickness of 2 nm, separated by interfaces that give the mineral expandable properties; see Kang et al (2012). Figure 6 compares whole-illite chemical analyses (Table 2) with the calculated composition of illite in borehole 29/10-2 at 4237À4356 m burial depth for different fundamental particle thicknesses using the model of Yates & Rosenberg (1998).…”
Section: Controls On Illite K-contentmentioning
confidence: 99%